Advances in immunology of obstructive sleep apnea: mechanistic insights, clinical impact, and therapeutic perspectives - Dong, Na; Yue, Hongmei (Frontiers in Immunology, 2025)
Obstructive sleep apnea (OSA) drives immune dysregulation through its hallmark stressors—intermittent hypoxia (IH) and sleep fragmentation (SF). Beyond impaired sleep, OSA acts as a systemic inflammatory trigger that disrupts immune homeostasis and reshapes both innate and adaptive responses. Recent evidence shows that OSA activates hypoxia-inducible factor-1α (HIF-1α), NF-κB signaling, and the NLRP3 inflammasome, promoting chronic inflammation and immune-cell dysfunction. These alterations mechanistically contribute to OSA-associated cardiovascular disease, metabolic disorders, cognitive impairment, and tumor progression. Reframing OSA as an immune-modulating disorder highlights the need for diagnostics and therapies guided by immunology rather than airway management alone.